Absolute and Relative Deprivation and the Measurement of Poverty - Jean-Yves Duclos; Philippe Grégoire (Luxembourg Income Study (LIS), 1999)
This paper develops the link between poverty and inequality by focusing on a class of poverty indices (some of them well-known) which aggregate normative concerns for absolute and relative deprivation. The indices are distinguished by a parameter that captures the ethical sensitivity of poverty measurement to 'exclusion' or 'relative-deprivation' aversion. We also show how the indices can be readily used to predict the impact of growth on poverty. An illustration using LIS data finds that the United States show more relative deprivation than Denmark and Belgium whatever the percentiles considered, but that overall deprivation comparisons of the four countries considered will generally necessarily depend on the intensity of the ethical concern for relative deprivation. The impact of growth on poverty is also seen to depend on the presence of and on the attention granted to concerns over relative deprivation.
Keywords: 330; Einkommensverteilung; Armut; Messung; Disparitätsmaß; Theorie